Sosialisasi dan Peningkatan Keterampilan dalam Pemanfaatan Bahan Pengawet Alami pada Produk Nugget di Desa Ngringo, Kecamatan Jaten, Kabupaten Karanganyar - Winny Swastike; Edi Suryanto; Jamhari Jamhari; Rio Olympias Sujarwanto (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2020)
The synthetic preservatives are often used in processing food and often found in the packaginginformation tables. Enhancing of dangerous preservatives such as formaldehyde and borax are also still found in food. Enchancing knowledge about the types of preservatives, the dosage and the dangers that can happen need to be done. This activity aims to improve knowledge and skills, especially in the utilization of natural preservatives in food processing. Participants in this activity were PKK cadres. This activity consists of 3 stages. The first stage was the socialization of preservatives, types of preservatives and the danger of using synthetic preservatives. The second activity was increasing knowledge of various types of natural preservatives around us that can be used in food processing. The third stage was the application of natural preservatives into the processed of chicken nugget. The success of this activity was seen from the increasing of indicators percentage that were used as parameters to determine the result. The conclusion obtained from this activity is that this activity can increase knowledge about the usage of natural preservatives in processed foods, especially nuggets, to replace synthetic preservatives.